Evaluation of access to the service provided by Primary Health Care in the Southwest Health Region I of the State of Goiás (Research, Society and Development, 2021)
The implementation of the principles of the Unified Health System is a major challenge for Primary Health Care, because it depends on the presence of health attributes. Access refers to the use of health services by the user, and when absent it can result in the low performance of the System and supposedly increase the rate of Hospitalizations for Conditions Sensitive to Primary Care. Objective: To evaluate the conditions of access to the service provided by Primary Health Care in the Southwest Health Region I. Materials and Methods: Cross-sectional study with a quantitative approach, carried out using secondary data referring to Hospitalizations for Conditions Sensitive to Primary Care extracted from the System of Hospital Information and application of the PCATool - Brazil instrument for patients hospitalized in public beds. Microsoft Excel was used for data refinement and a statistical program for descriptive analysis. Results: There were 19,993 Hospitalizations for Sensitive Conditions in the municipality of Rio Verde in the period from 2010 to 2019. The diagnoses of heart failure, bacterial pneumonia, infectious gastroenteritis and complications, kidney and urinary tract infection and lung diseases prevailed. Of the 260 respondents between April / 2019 and March / 2020, 51.92% refer to adults and 48.07% to children; 77% did not have any degree of PHC affiliation. Conclusion: Access to the service provided by PHC in the studied region is unsatisfactory, requiring the reformulation of public policies, programs and health actions that are being developed in order to increase coverage in the region.